Implementation of Job Shadowing Learning Model Towards Task Skill Practice of Normal Delivery Care for Students of Midwifery - Sherly Vermita Warlenda; Hastuti Marlina (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to determine the effectiveness of the job shadowing learning model in the practice of normal delivery care for task skills. This type of quantitative research has a quasi-experimental pre- and post-test design. The sample size is 33 people. The collection used a task-skill questionnaire about normal delivery care. The task skill components measured include task management skills (TMS), work environment skills (WES), interpersonal skills (IS), and workplace learning skills (WLS). The results showed a difference in the average pre-test, post-test 1, and post-test 2 task skills, which experienced an increase. Statistically, the t-dependent test shows a p-value of 0.000, meaning that the job shadowing learning model in normal delivery care effectively increases task skills. It is hoped that midwifery education institutions will strengthen the evaluation of learning about normal delivery care practices through the job shadowing learning model by paying attention to the task skill aspect. This requires increased external cooperation, such as maternity homes and hospitals, as places for midwifery students to apply their knowledge.